FAILURE OF THE HEART DETERMINATION PROTEOMIC PROFILING RELATED TO PATIENTS WHO ARE ELDERLY - Yuldashev Soatboy Jiyanboevich; Imran Aslam; Jiyanboyev Nodirbek Soatboyevich (Research Focus International Scientific Journal, 2024)
Objective These eighty proteins have been identified to be connected with cardiovascular pathology in the past, and the purpose of this study paper is employing proteomic profiling of these proteins in order to discover new risk factors for heart failure or heart failure in general. Materials and Methods Analyses of the proximity extension (Proteomic profiling) has been performed in two different communities with varying cohorts in the elderly at the baseline in the absence of cardiac failure. The prospective of the research were Prospective Investigation of the Vasculature (PIV) and Longitudinal Study of Adult Men (LSAM) having respective values (80 events, median age = 70.2 years, n = 901) and (90 events, median age = 77.8 years, n = 685). Incident of heart failure was associated with 29 proteins as observed in PIV with adjusted sex and age. Corrections were made after multiple tests. In LSAM there were 18 proteins associated with heart failure. High level of 9 proteins were related to the incident of heart failure among both the cohorts. There were additional modifications made to the established risk variables. There was a deficit in the left ventricular systolic function that was found to be associated with the presence of growth differentiation factor 15 (GDF-15), urokinase-type plasminogen activator surface receptor (U-PAR), matrix metalloproteinase-12 (MMP-12), tumour necrosis factor-related apoptosis-inducing ligand receptor 2 (TRAIL-R2), spondin-1 (SPON1), and follistatin (FS). This was discovered through echocardiographic monitoring. Each and every one of the P values was lower than 0.02. Results The final characteristics of PIV included median age of 70 years among a total of 901 participants. In LSAM the characteristic showed median age of 78 years among 685 participants. During follow-up among PIV the age range was 0.1-10.9 years with a median of 10 years, 80 hospitalizations due to heart failure with a heart failure rate of 0.96 among 100 persons. There were 90 hospitalisations for heart failure among LSAM, the age range was 0.2-10.9 years with a median of 8 years, and the heart failure rate was 1.83 per 100 people. False discovery rate among PIV was 5% with the association of 29 proteins after adjusted sex and age. Among LSAM the association of 18 proteins was nominal for the incident of heart failure. Conclusion Several novel associations for the involvement of proteins in fibrinolysis, apoptosis, inflammation, matrix remodeling and heart failure were identified through Proteomic profiling in the research study among elderly. The outcomes of this research also correspond to other investigations that studied underlying clinical utilities and mechanisms.